TRANSFORMASI INOVASI PEMBELAJARAN GURU MELALUI PERILAKU ORGANISASI SEKOLAH DI SMTK BENFOMENI KAPAN - Marya Dorince Christiana; Erni Murniarti (STKIP Pesisir Selatan, 2026)
This research focuses on the Benfomeni Kapan Vocational High School, located in North Mollo District, South Central Timor Regency, East Nusa Tenggara (NTT). The educational context in NTT, particularly in areas like TTS, often faces specific challenges, including limited resources and geographical conditions. The culture within a school will shape teachers to create quality learning. However, in practice, there are still some teachers who have not maximized this learning. This qualitative study using a case study method focused on examining the influence of school organizational behavior (including leadership, culture, communication, motivation, and teamwork) on teacher learning innovation at SMTK Benfomeni Kapan. Teacher innovation is a vital indicator in the context of Christian education, which must adapt to changes in curriculum and technology. The results of the study indicate a strong relationship: positive and participatory organizational behavior oriented towards human resource development has been shown to significantly increase teacher creativity and learning innovation. Meanwhile, a rigid organizational environment, closed communication, and lacking structural support tend to hinder teachers' innovative efforts. This research, which uses data from in-depth interviews, observations, and documentation, is expected to guide management improvements and enhance the quality of education at SMTK.